1989
DOI: 10.1176/ajp.146.2.148
|View full text |Cite
|
Sign up to set email alerts
|

A neuroanatomical hypothesis for panic disorder

Abstract: Anxiety disorders, the most common psychiatric conditions in the United States, have generated a great deal of research and scientific debate. Panic disorder, the best-studied anxiety disorder, is often believed to be either a biological disease or a psychological disease. The authors present a neuroanatomical model of panic disorder that attempts to reconcile these views. The model locates the three components of the disease--the acute panic attack, anticipatory anxiety, and phobic avoidance--in three specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 329 publications
(24 citation statements)
references
References 93 publications
1
23
0
Order By: Relevance
“…Attempting to explain clinical observations that both pharmacological intervention and cognitive behavioral therapy are successful in treating PD, Gorman and colleagues (1989b) posited a neuroanatomical hypothesis of panic consisting of a network of cortical, limbic and brainstem structures implicated in mediating the phobic avoidance, anticipatory anxiety and panic attacks observed in PD patients; the neuroanatomical hypothesis of PD was revised based on preclinical rodent models identifying the neural structures mediating fear-conditioning and avoidance behavior (Gorman et al, 2000). As Klein has repeatedly indicated (Klein, 1993;Klein, 2002;Preter and Klein, 2008), although panic and fear share many characteristics they have important physiological distinctions such as the lack of HPA-axis activation in panic (Hollander et al, 1989;Kellner and Wiedemann, 1998;Levin et al, 1987;Woods et al, 1988), which is a common neuroendocrine response to fear-related stimuli like exposure to a predator (Blanchard et al, 1998), predator odor (Masini et al, 2005;Masini et al, 2006), or conditioned fear (Cordero et al, 1998), and the presence of dyspnea in panic, which rarely occurs in natural fear responses (Klein, 1993;Preter and Klein, 2008).…”
Section: Introduction To Panic Disordermentioning
confidence: 99%
“…Attempting to explain clinical observations that both pharmacological intervention and cognitive behavioral therapy are successful in treating PD, Gorman and colleagues (1989b) posited a neuroanatomical hypothesis of panic consisting of a network of cortical, limbic and brainstem structures implicated in mediating the phobic avoidance, anticipatory anxiety and panic attacks observed in PD patients; the neuroanatomical hypothesis of PD was revised based on preclinical rodent models identifying the neural structures mediating fear-conditioning and avoidance behavior (Gorman et al, 2000). As Klein has repeatedly indicated (Klein, 1993;Klein, 2002;Preter and Klein, 2008), although panic and fear share many characteristics they have important physiological distinctions such as the lack of HPA-axis activation in panic (Hollander et al, 1989;Kellner and Wiedemann, 1998;Levin et al, 1987;Woods et al, 1988), which is a common neuroendocrine response to fear-related stimuli like exposure to a predator (Blanchard et al, 1998), predator odor (Masini et al, 2005;Masini et al, 2006), or conditioned fear (Cordero et al, 1998), and the presence of dyspnea in panic, which rarely occurs in natural fear responses (Klein, 1993;Preter and Klein, 2008).…”
Section: Introduction To Panic Disordermentioning
confidence: 99%
“…Indeed, confusion can also occur with respect to what has been called chronic hyperventilation syndrome [330], panic disorder [331,332], hyperventilation induced seizures [333], phobic anxiety depersonalization syndrome [293] and Rett’s syndrome [334]. Hyperventilation induced seizures, albeit rarely tonic-clonic or partial [333], has been the subject of many case reports [300,329,335].…”
Section: Discussionmentioning
confidence: 99%
“…Gorman et al[10] introduced a neuroanatomical model that was aimed at integrating the different views of PD as either a biological or a psychological disease. The authors suggested experiments to test their theories.…”
Section: Introductionmentioning
confidence: 99%
“…According to Gorman et al[10] three components of PD: (1) acute panic attacks, (2) anticipatory anxiety; and (3) phobic avoidance are located in three specific sites of the CNS: The brainstem, limbic system, and prefrontal cortex. These three neural systems were suggested to be structurally and functionally closely connected, reflecting manifold interactions of the three mentioned clinical features.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation